Analysis of User Satisfaction Virtual Reality Tourism Kemenparekraf Using the End User Computing Satisfaction Method - Pingki Pingki; Wira Bharata (Jurnal Teknologi Informasi dan Pendidikan, 2023)
Virtual Reality (VR) has developed on the concept of tourism where people can enjoy virtual tourist destinations called VR Tourism. The tourism industry, one of which is Indonesia, is utilizing this technology development as a marketing strategy for tourist objects, one of which is VR Tourism Kemenparekraf. Previous research on how VR affects marketing has been carried out a lot, but this research will focus on user responses to VR Tourism services which are still little done. From this, by utilizing the End User Computing Satisfaction (EUCS) method, it is used to measure the satisfaction of VR Tourism Kemenparekraf users, as well as to see whether this method is still relevant to use. Respondents were determined as many as 75 people who had used VR Tourism Kemenparekraf at least once. The data was processed using SPSS software, where the research results found that all variables contained in the EUCS method had a positive effect on user satisfaction. Users are satisfied with VR Tourism Kemenparekraf. The EUCS method is still relevant for use in testing user satisfaction in VR Tourism Ministry of Tourism and Creative Economy.